1502. Psychological Stress and Anxiety among Parents of Children Younger than 5 Years Hospitalized with RSV. (31st December 2020) - Ampofo, Krow; Choi, Yoonyoung; Heller, Evan G; Platt-Koch, Alexander G; Gesteland, Per H; Adua, Lazarus; Finelli, Lyn
Abstract: Background: Respiratory Syncytial Virus (RSV) is one of the most common causes of childhood lower respiratory tract infection (LRTI) worldwide. While financial burdens have been documented, there are few data on parental psychological stress associated with RSV hospitalizations. We evaluated the psychological stress and anxiety of parents whose children were hospitalized with RSV. Methods: During the 2019-2020 RSV season, parents with children < 5 years of age hospitalized with laboratory-confirmed RSV LRTI at Primary Children's and Riverton Hospitals in Salt Lake City, Utah, were surveyed in person, and online after discharge. As part of the survey, parents completed the State-Trait Anxiety Inventory for Adults (STAIAD) instrument (short form) and the parental stressor scale (PSS). We evaluated the difference in parental stress and anxiety reported during hospitalization and at 2-weeks post-discharge using a paired t-test. Results: Among 284 Salt Lake County resident children < 5 years, and hospitalized with RSV LRTI, 75 (26%) and 57 (20%) parents completed both surveys on admission and at 2-weeks post-discharge respectively. In 11 of 20 STAIAD items gauging stress and anxiety, parents reported higher levels of stress and anxiety whilst their children were admitted compared to post-discharge (Table 1 ). Parents' average score on several items associated with a "positive outlook, " e.g. I feel calm, significantly improved (p < 0.05) at 2-weeks post-discharge. Similarly, several items associated with a "negative outlook, " e.g. I am worried, significantly decreased (p < 0.05) at 2-weeks post-discharge (Table 1 ). For the PSS items, ≥ 50% of parents rated 15 out of 25 as being "very or extremely stressful", including: feeling helpless about how to help my baby; my baby's unusual or abnormal breathing; and when my baby seemed to be in pain (Table 2) . Estimates of Psychological Burden of RSV lower respiratory tract infection (LRTI) Hospitalization of Children <5 Years of Age on Parents: State-Trait Anxiety Inventory for Adults (STAIAD) Estimates of Psychological Burden of RSV lower respiratory tract infection (LRTI) Hospitalization of Children <5 Years of Age on Parents: Parental Stressor Scale (PSS) Conclusion: RSV LRTI hospitalization among children < 5 years of age, imposed a significant psychological stress and anxiety on parents, which generally persisted up to 2-weeks post-discharge. Prevention of RSV infection through vaccines and immunoprophylaxis will help ease parental psychological burden associated with RSV hospitalization. Disclosures: Krow Ampofo, MBChB, Merck (Grant/Research Support) Yoonyoung Choi, PhD, MS, RPh, Merck (Employee) Lyn Finelli, DrPH, MS, Merck & Co Inc, (Employee)